2006
DOI: 10.1021/ie0511027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Product Solutions of tert-Butyl Alcohol Dehydration in Reactive Distillation

Abstract: The feasibility of tert-butyl alcohol (TBA) dehydration to selectively produce the high purity products isobutene or diisobutene by using reactive distillation has been illustrated through process simulations. Correspondingly, different column configurations are proposed. The influence of the important operating parameters on the column performance is analyzed by continuation methods, and the operating windows of the parameters are suggested. Advantages of employing reactive distillation for TBA dehydration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This result indicated that no oxidation occurred for t‐butanol because of its relatively stable chemical properties. It was reported that tert‐butanol tends to dehydrate and becomes isobutene in hot acid environment . This is in agreement with the FTIR results shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…This result indicated that no oxidation occurred for t‐butanol because of its relatively stable chemical properties. It was reported that tert‐butanol tends to dehydrate and becomes isobutene in hot acid environment . This is in agreement with the FTIR results shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The conclusion was restated by Zhao et al [19] through their experimental investigation and theoretical simulation. Due to the importance of reactive distillation in an organic CHP, more and more attention has been paid to the reactive distillation process of tert-butanol, including rectifying process analysis, thermodynamic and kinetic analysis, experimental investigation, modeling, and simulation [50,51,[54][55][56][57].…”
Section: Reactive Distillationmentioning
confidence: 99%
“…The basic process design is illustrated in Figure , which contains a decomposition reaction (A ↔ B + C). Similar practical processes include the decomposition of tert -butyl alcohol and cumene hydroperoxide. , The process accommodates a three-zone structure, 8/12/4, and the feed location of reactant A is arranged at the middle of the reactive section, because it is the intermediate substance among all the reacting components. The specifications are set to be 98 mol % for products B and C, respectively.…”
Section: Example Iv: a Hypothetical Ternary Reactive Distillation Sys...mentioning
confidence: 99%